The Role of Customer Journey in Building Positive Emotions through Customer Experience in E-Dabu BPJS - Ni Putu Nina Nuryati; I Gusti Ngurah Agung Gede Eka Teja Kusuma; Ni Putu Cempaka Dharmadewi Atmaja (International Journal of Economics and Management Sciences, 2025)
The increasing participation in JKN in Denpasar has prompted BPJS Kesehatan to optimize the use of e-Dabu; however, the service continues to face persistent technical and usability challenges. Ongoing system issues, limited user proficiency, and unsatisfactory user experiences have reduced engagement with e-Dabu, highlighting the importance of understanding how the customer journey shapes positive emotions and customer passion through customer experience. This quantitative study employs validated measurement scales covering e-Dabu, customer journey, positive emotions, customer passion, and customer experience, with a sample of 190 business entity PICs at the BPJS Kesehatan Denpasar Branch. Data were analyzed using the SEM-PLS method, and the findings reveal that customer journey and positive emotions significantly influence customer experience. Additionally, positive emotions and customer experience significantly affect customer passion, while customer journey does not directly impact customer passion. The study concludes that enhancing customer journey, positive emotions, and customer experience is essential for increasing customer passion within BPJS Kesehatan Denpasar. These findings offer valuable theoretical and practical contributions to improving digital public service management.